Computer aided simulation for non-linear model of ship motion - Le, Nguyen Nhat (Vietnam Journal of Mechanics, 1994)
The ship motion is simulated on computer by non-linear model of small vibration and strong non-linear model. The results are compared between two models. The influences of different parameters to the ship motion are considered.